The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.jpsychires.2017.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinic modulation of salience network connectivity and centrality in schizophrenia

Abstract: Although functional abnormalities of the salience network are associated with schizophrenia, the acute effects of nicotine on its function and network dynamics during the resting state in patients are poorly understood. In this study, the effects of a 7 mg nicotine patch (vs. placebo) on salience network connectivity were examined in 17 patients with schizophrenia and 19 healthy subjects. We hypothesized abnormal connectivity between the salience network and other major networks (e.g. executive network) in pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 93 publications
(120 reference statements)
0
8
0
Order By: Relevance
“…Similar to LEP responses, vertex potentials elicited by intense stimuli belonging to different sensory modalities (Mouraux & Iannetti, ) largely reflect saliency‐related neural processes possibly related to the detection of relevant changes in the sensory environment (Downar, Crawley, Mikulis, & Davis, ). Considering that N2 wave is mainly generated from the insula that is an interoceptive integration brain structure playing a crucial role in the salience network, as it conveys multisensory information about internal body state and external surrounding environment (Craig, ), previous studies suggested that dysfunction of sensory information processing across modalities in SCZ patients could represent an epiphenomenon of salience network dysfunctions (Alustiza et al, ; Liddle et al, ; Minichino et al, ; Palaniyappan & Liddle, ; Potvin et al, ; Smucny, Wylie, Kronberg, Legget, & Tregellas, ). The salience network is involved in detecting and filtering salient stimuli and functions to segregate the most prominent information among internal and external stimuli in order to guide behavior (Legrain, Iannetti, Plaghki, & Mouraux, ; Mouraux, Diukova, Lee, Wise, & Iannetti, ).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to LEP responses, vertex potentials elicited by intense stimuli belonging to different sensory modalities (Mouraux & Iannetti, ) largely reflect saliency‐related neural processes possibly related to the detection of relevant changes in the sensory environment (Downar, Crawley, Mikulis, & Davis, ). Considering that N2 wave is mainly generated from the insula that is an interoceptive integration brain structure playing a crucial role in the salience network, as it conveys multisensory information about internal body state and external surrounding environment (Craig, ), previous studies suggested that dysfunction of sensory information processing across modalities in SCZ patients could represent an epiphenomenon of salience network dysfunctions (Alustiza et al, ; Liddle et al, ; Minichino et al, ; Palaniyappan & Liddle, ; Potvin et al, ; Smucny, Wylie, Kronberg, Legget, & Tregellas, ). The salience network is involved in detecting and filtering salient stimuli and functions to segregate the most prominent information among internal and external stimuli in order to guide behavior (Legrain, Iannetti, Plaghki, & Mouraux, ; Mouraux, Diukova, Lee, Wise, & Iannetti, ).…”
Section: Discussionmentioning
confidence: 99%
“…We did not find any significant effects of nicotine on resting state functional connectivity measures, consistent with our prior research in smokers with and without schizophrenia in which there was no effect of nicotine on the strength of functional connectivity between dACC and striatal regions (Moran et al 2012). However, a recent study using graph theoretical methods found enhanced nicotine-induced connectedness of the ACC in individuals with schizophrenia but the opposite effect of nicotine in healthy individuals (Smucny et al 2017). Our finding of negative correlations between right caudate activation and connectivity between right caudate and dACC/DLPFC suggests that enhanced nicotine-induced caudate activation in response to errors served as a compensatory mechanism to overcome functional dysconnectivity in the cognitive control network in schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…Our laboratory has recently expanded upon this work by examining effects of acute nicotine on resting state SN connectivity and topology in nonsmoking schizophrenia patients and healthy controls (Smucny et al, 2017). The SN was extracted by independent component analysis, and peaks from the extracted network used as seeds in a functional connectivity analysis.…”
Section: Nicotinic Agonists Modulate Brain Network In Schizophreniamentioning
confidence: 99%